Economic evaluation of low-voltage devices - Havrys, Oleksandr M.; Havrys, Olha O. (Національний технічний університет "Харківський політехнічний інститут", 2023)
Modern electrical products represent an extremely powerful industry and a dynamically developing market. Currently, there is a positive trend in the market, in particular for low-voltage devices, so an important aspect is to conduct a correct economic assessment of the efficiency of low-voltage devices. Literary sources are analyzed and it is revealed that, despite the significant amount of scientific research and publications, in scientific workson economic design, insufficient attention is paid to the study of real conditions and operating modes of products. Related works focus on developing numerical methods for solving the problem, and the usage conditions are usually taken as given. Data are presented on the actual use of the main parameters of automatic and push-button switches in the main conditions and modes of their use on the equipment of machine-building enterprises. Similar data were also obtained in metallurgy. In addition, a more in-depth study is required of the practical use of the main indicators of purpose and reliability, analysis of operating costs in specific conditions of use and features of economic assessment. The purpose of the study is to analyze issues of improving methods for economic evaluation of one of the most common types of electrical products -low voltage devices. Studies have been carried out on the actual use of indicators of purpose and durability, operating costs for scheduled and unscheduled repairs in real modes and operating conditions, losses due to failures. Improved indicators and criteria for economic evaluation are proposed. The possibilities of using both traditional economic assessment based on reduced costs, as well as economic assessment and criteria for choosing rational levels based on indicators more often used in modern conditions, including NPV, PI, IRR, PP, are considered. When solving the problem of economic justification for choosing a rational number of versions of devices, several main stages are identified. Among them is the choice of economic indicator and criterion.
Економічна оцінка апаратів низької напруги
Keywords: economic evaluation; operating costs; operating modes; low voltage devices; failure losses